Cancer-Specific and All-Cause Mortality in Kidney Transplant Recipients With and Without Previous Cancer. Issue 12 (December 2015) - Viecelli, Andrea K.; Lim, Wai H.; Macaskill, Petra; Chapman, Jeremy R.; Craig, Jonathan C.; Clayton, Philip; Cohney, Solomon; Carroll, Robert; Wong, Germaine
Abstract : Background: For dialysis patients with a cancer history, a period of surveillance is generally recommended before listing for transplantation. However, the outcomes of patients with cancer recurrence and/or a second primary cancer after transplantation are unknown. Aim: To determine the prognosis of kidney transplant recipients who developed cancer after transplantation and whether this varied with cancer types (first cancer, recurrence, second primary cancer). Methods: Using data from the Australian and New Zealand Dialysis and Transplant Registry, we compared the cancer-specific and all-cause mortality among recipients with different cancer types using adjusted Cox proportional hazard models. Results: Of the 21, 415 recipients transplanted between 1965 and 2012, 3% (651 of 21, 415) had a previous cancer history. A total of 2840 (13%) recipients developed cancer after the first transplant, of whom 2760 (97.2%) developed a first cancer, 23 (0.8%) experienced cancer recurrence, and 57 (2%) developed a second primary cancer. There were no significant differences in the risks of cancer-specific and all-cause mortality between recipients who developed their first cancer after transplant, those with cancer recurrence (adjusted hazard ratios [aHRs], 0.79; 95% confidence interval [95% CI], 0.38-1.67; P = 0.54 and aHRs, 0.86; 95% CI, 0.45-1.66; P = 0.66, respectively) and recipients who developed a second primary cancer after transplantation (aHRs, 1.01; 95%CI, 0.63-1.62; P = 0.95 and aHRs, 1.16; 95% CI, 0.79-1.69; P = 0.45, respectively). Conclusion: Among patients with a previous history of malignancy, recurrent and second primary cancers are infrequent after renal transplantation. A history of previous malignancy does not have an additive effect on the cancer-specific and overall survival of kidney transplant recipients who develop cancer. Abstract : Using data from the ANZDATA registry, the authors demonstrate that cancer-specific and all-cause mortality are similar in patients who develop a first cancer after kidney transplantation and in the rare patient with a prior cancer history whether they experience cancer recurrence or a second primary cancer.